2023
DOI: 10.1101/2023.01.05.23284217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Value of Admission Avoidance: Cost-Consequence Analysis of One-Year Activity in a Consolidated Service

Abstract: Background: Many advantages of hospital at home (HaH), as a modality of acute care, have been highlighted, but controversies exist regarding the cost-benefit trade-offs. Objective: To assess health outcomes and analytical costs of hospital avoidance (HaH-HA) in a consolidated service with over ten years of delivery of HaH in Barcelona (Spain). Methods: A retrospective cost-consequence analysis of all first episodes of HaH-HA, directly admitted from the emergency room (ER) between 2017 and 2018, was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…As described above, all economic calculations in the current study were based on expenditure data. 31 However, we believe that the characteristics of the study design and the availability of clinical and analytical data from the area 32,33 positively influenced the analyses carried out in the current research and facilitated recommendations for enhancing the quality of service delivery that can be generalized to other integrated care services.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As described above, all economic calculations in the current study were based on expenditure data. 31 However, we believe that the characteristics of the study design and the availability of clinical and analytical data from the area 32,33 positively influenced the analyses carried out in the current research and facilitated recommendations for enhancing the quality of service delivery that can be generalized to other integrated care services.…”
Section: Discussionmentioning
confidence: 98%
“…A recently reported contemporary assessment of analytical costs in the Hospital Clinic of Barcelona, one of the leading public healthcare providers in the area, demonstrated that AA generates substantial savings, reducing operational costs by half, mainly due to personnel and structure costs. 32,33 In this regard, it must be emphasized that expenses during the episode of AA, based on APR-DRGs, do not correspond with the operational costs of the intervention. The expert group agreed that the implementation of analytical accounting should be extended to all providers to build up adequate reimbursement strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, all economic calculations in the current study were based on expenditure data. 32 However, we believe that the characteristics of the study design and the availability of clinical and analytical data from the area 33,34 positively in uenced the analyses carried out in the current research and facilitated recommendations for enhancing the quality of service delivery that can be generalized to other integrated care services.…”
Section: Study Limitationsmentioning
confidence: 97%
“…Expenditure information was obtained from reimbursements by the Catalan Health Service, 32 since no operational costs 33,34 were available for the entire study group. HaH delivery is reimbursed as a speci c healthcare service, with case costs estimated based on the APR-DRG categories of the main diagnostic.…”
Section: Variables and Outcomesmentioning
confidence: 99%